Comprehensive strategy to reduce the incidence of lead dislodgement for cardiac implantable electronic devices. Issue 1 (29th November 2018) - Afzal, Muhammad R.; Horner, Sarah; Matre, Nancy B.; Blake, Patricia; Dunham, Kari; Pinkhas, Daniel; Okabe, Toshimasa; Tyler, Jaret; Houmsse, Mahmoud; Kalbfleisch, Steven J.; Weiss, Raul; Hummel, John D.; et al.
Abstract: Background: Lead dislodgement (LD) is a well‐recognized complication during implantation of cardiac implantable electronic devices (CIEDs). An intraprocedural protocol, referred to as reduction of LD protocol, was developed to reduce the risk of LD. Methods: The protocol involved (1) inserting a straight stylet down the right atrial lead and applying forward pressure while monitoring for fluoroscopic stability, (2) visualizing all leads during deep inspiration to determine if there is adequate lead redundancy, and (3) having the patient take a deep breath and cough while pacing just at capture threshold to assess for loss of capture in each lead. Any intraprocedural change in the parameters fulfilling the predefined criteria for inadequate lead implantation prompted lead repositioning. Data regarding demographic factors, clinical characteristics, and incidence of LD in the first 30 days after implant was obtained from intramural CIED database. The preintervention (control) group spanned 27 months and consisted of a total of 4, 294 leads while the postintervention (intervention) group spanned 17 months and consisted of 2, 361 leads implanted. Results: There was no significant difference in the demographic factors and clinical characteristics in the two groups. Protocol compliance was > 90%. There were 44 occurrences of LD (1.02%) before and 10 (0.4%) after implementation of the protocol. The protocol significantly reduced the incidence of LD during the 30 days after implant (P = 0.014). No clinical characteristic predicted the risk of LD. Conclusion: Intraprocedural maneuvers performed to assess the adequacy of lead implantation results in reduced risk of LD.